Edukasi Upaya Pencegahan Hipertensi melalui Pola Makan Seimbang - Aisah, Aisah; Putri, Satiti Kawuri (Universitas Baiturrahim, 2025)
Hypertension is one of the non-communicable diseases (NCDs) which is a very serious health problem both in the world and in Indonesia. Hypertension is called a silent killer, because people with hypertension often do not show symptoms. Wrong diet is one of the risk factors that increase hypertension. Modern food factors are the main contributors to hypertension. Several factors that can cause someone to suffer from blood pressure, namely factors that cannot be changed are age, heredity, gender and factors that can be changed are exercise, diet, obesity, drinking alcohol, stress. Based on research data that has been conducted by the author at the Rawasari Health Center, there is a relationship between diet and hypertension. The implementation of Community Service activities was carried out from March to August 2023, with the aim of Community Service Activities being to provide and increase education to participants in efforts to prevent hypertension through a balanced diet. The implementation of this education was carried out in a way using leaflet and power point media and measuring participant knowledge by conducting pre and post tests. In addition to behavioral changes, another expected outcome is the publication of activity results in accredited public health journals. It is knownThe pre-test results obtained an average of 34% correct answers and 66% wrong answers, there was an increase in participant knowledge seen from the post-test results where the average correct answer was 75% and 25% incorrect answers. The provision of counseling is expected to increase understanding of balanced nutrition and eating patterns related to hypertension so that it is expected to be practiced in everyday life.